Efforts to Improve Character Development and Discipline at Raudlatul Ulum Islamic Boarding School through Community Empowerment and Guidance - Abdullah Hilmi Azzuhdy; Hidayatullah Hidayatullah (Pelangi (e-Journal), 2026)
Islamic boarding schools (pesantren) play a strategic role in shaping the character and discipline of their students, serving not only as centers of religious knowledge but also as centers of moral and ethical development. However, at the Raudlatul Ulum Islamic Boarding School, this development faces challenges such as a lack of student awareness, weak disciplinary controls, and external influences, particularly in the digital age. To address these challenges, community mentoring has been identified as an appropriate solution. This study aims to analyze the effectiveness of the community mentoring program in improving character development and discipline among students at the Raudlatul Ulum Islamic Boarding School. The research also identifies challenges faced and strategies for program optimization. Through holistic mentoring involving various parties, it is hoped that there will be significant improvements in students' morals, independence, responsibility, and time management, as well as the creation of strong collaboration between the Islamic boarding school and the community. A conducive educational environment is also expected to equip students with life skills and psychological well-being, preparing them to become responsible individuals who contribute to society.